Production, extraction and characterization of Chlorella vulgaris soluble polysaccharides and their applications in AgNPs biosynthesis and biostimulation of plant growth - El-Naggar, Noura El-Ahmady; Hussein, Mervat H.; Shaaban-Dessuuki, Sami A.; Dalal, Shimaa R. (Scientific reports, 2020)
Chlorella vulgaris , like a wide range of other microalgae, are able to grow mixotrophically. This maximizes its growth and production of polysaccharides (PS). The extracted polysaccharides have a complex monosaccharide composition (fructose, maltose, lactose and glucose), sulphate (210.65 ± 10.5 mg g −1 PS), uronic acids (171.97 ± 5.7 mg g −1 PS), total protein content (32.99 ± 2.1 mg g −1 PS), and total carbohydrate (495.44 ± 8.4 mg g −1 PS). Fourier Transform infrared spectroscopy (FT-IR) analysis of the extracted polysaccharides showed the presence of N–H, O–H, C–H, –CH 3 , >CH 2 , COO −1 , S=O and the C=O functional groups. UV–Visible spectral analysis shows the presence of proteins, nucleic acids and chemical groups (ester, carbonyl, carboxyl and amine). Purified polysaccharides were light green in color and in a form of odorless powder. It was soluble in water but insoluble in other organic solvents. Thermogravimetric analysis demonstrates that Chlorella vulgaris soluble polysaccharide is thermostable until 240°C and degradation occurs in three distinct phases. Differential scanning calorimetry (DSC) analysis showed the characteristic exothermic transition of Chlorella vulgaris soluble polysaccharides with crystallization temperature peaks at 144.1°C, 162.3°C and 227.7°C. The X–ray diffractogram illustrated the semicrystalline nature of these polysaccharides. Silver nanoparticles (AgNPs) had been biosynthesized using a solution of Chlorella vulgaris soluble polysaccharides. The pale green color solution of soluble polysaccharides was turned brown when it was incubated for 24 hours with 100 mM silver nitrate in the dark, it showed peak maximum located at 430 nm. FT-IR analysis for the biosynthesized AgNPs reported the presence of carbonyl, –CH 3 , >CH 2 , C–H,–OH and –NH functional groups. Scanning and transmission electron microscopy show that AgNPs have spherical shape with an average particle size of 5.76. Energy-dispersive X-ray (EDX) analysis showed the dominance of silver. The biosynthesized silver nanoparticles were tested for its antimicrobial activity and have positive effects against Bacillus sp., Erwinia sp., Candida sp. Priming seeds of Triticum vulgare and Phaseolus vulgaris with polysaccharides solutions (3 and 5 mg mL −1 ) resulted in significant enhancement of seedling growth. Increased root length, leaf area, shoot length, photosynthetic pigments, protein content, carbohydrate content, fresh and dry biomass were observed, in addition these growth increments may be attributed to the increase of antioxidant activities.